Geological Investigation of Clay Minerals (Swelling) Pt. Upb Antam Pongkor Bogor, West Java, Indonesia - Gevor, Even; Indrawan, I Gde Budi; Warmada, I Wayan (Journal of Applied Geology, 2024)
Rocks containing clay minerals can experience rock deformation when interacting with water, this can also caused by the argillic zone, in the underground tunnel at the Unfoloader 600 and Xc 600 loop 2 ciurug. The argillic process that causes actual material swelling that occurs in field causes rock mass around the mining development area to become weak. The location from tunnel cross cut of Unfoloader 600 and Xc 600 loop 2 contain active clay minerals which high percentage composition of swelling mineral material. The Unfoloader 600 location has a mineral swelling composition of 102.94% with 24 hours, justifying potential very high swelling. The minerals present based on XRD testing 70.8% illite, 25.4% kaolinite, 25.4% kaolinite and 3.8% montmorillonite. Location Xc 600 loop 2 has a mineral swelling composition of 131.25% with 24 hours, justifying potential for very high swelling. The minerals present based on XRD testing illite 49.7%, kaolinite 28.7%, quartz 20.3%, and montmorillonite 1.2%. The values obtained based on laboratory form free swelling tests and XRD that the location experienced of rock deformation, it’s swelling in the mining development area.